2019
DOI: 10.1002/tcr.201800160
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of π‐Conjugated Benzocyclotrimers

Abstract: Polycyclic aromatic hydrocarbons (PAHs), especially three branchphene benzocyclotrimers represent a series of molecules with intriguing physical and chemical properties. Benzocyclotrimers are also important precursors to construct fullerenes and graphenes. In this article, we review the recent progress in the preparation methods of p-conjugated benzocyclotrimers. In particular, cyclotrimerization reactions to construct varying shaped and edged benzocyclotrimers are illustrated. Various typical characterization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…The most applied synthetic strategy towards these soluble starphenes is a palladium-catalysed [2+2+2] cycloaddition reaction of in situ generated arynes from appropriate arene derivatives. [11][12][13] Another often used approach is a nickel-mediated Yamamoto coupling reaction of ortho-dibrominated arenes. [2,6,10,14] As an alternative, on-surface synthesis (OSS) in ultra-high vacuum (UHV) allows the preparation, although in minute amounts, of organic structures that are hardly attainable by traditional in-solution chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…The most applied synthetic strategy towards these soluble starphenes is a palladium-catalysed [2+2+2] cycloaddition reaction of in situ generated arynes from appropriate arene derivatives. [11][12][13] Another often used approach is a nickel-mediated Yamamoto coupling reaction of ortho-dibrominated arenes. [2,6,10,14] As an alternative, on-surface synthesis (OSS) in ultra-high vacuum (UHV) allows the preparation, although in minute amounts, of organic structures that are hardly attainable by traditional in-solution chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Two features make this transformation particularly interesting for the preparation of large PAHs and nanographenes: (1) the ready availability of ortho -(trimethylsilyl)­aryl triflates to be used as precursors of substituted or polycyclic arynes and (2) the significant increase in the molecular complexity in one single step, that is, the easy preparation of structures formed by 3 n + 1 cycles starting from molecules with n cycles. Herein we have selected some examples of Pd-catalyzed aryne cyclotrimerizations to illustrate the potential of this methodology for the preparation of trigonal PAHs and nanographenes. , …”
Section: Introductionmentioning
confidence: 99%
“…Herein we have selected some examples of Pd-catalyzed aryne cyclotrimerizations to illustrate the potential of this methodology for the preparation of trigonal PAHs and nanographenes. 11,12 ■ SYNTHESIS OF SUBSTITUTED TRIPHENYLENES Soon after the discovery of the Pd-catalyzed aryne cyclotrimerization, it was found that a large variety of transition metal complexes are capable of promoting this transformation. For example, it was reported that Ni(0), 9 Cu(I), 13 and Au(I) 14 complexes can efficiently promote the cyclotrimerization of benzyne.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently,B unz et al have prepared [13]-and [16]starphene derivatives with bulky triisopropylsilyl-ethynyl groups, [10] which are the longest substituted starphenes prepared to date.H owever,t hese bulky substituents can modify the electronic properties of the molecules,t heir packing and moreover affect interactions with metal surfaces,w hich can be limiting factors in the applications of the substituted starphenes in organic and single-molecule electronics.T he most applied synthetic strategy towards these soluble starphenes is ap alladiumcatalysed [2+ +2+ +2] cycloaddition reaction of in situ generated arynes from appropriate arene derivatives. [11][12][13] Another often used approach is anickel-mediated Yamamoto coupling reaction of ortho-dibrominated arenes. [2,6,10,14] As an alternative,on-surface synthesis (OSS) in ultra-high vacuum (UHV) allows the preparation, although in minute amounts,o fo rganic structures that are hardly attainable by traditional in-solution chemistry.…”
Section: Introductionmentioning
confidence: 99%